Efficacy and Adverse Events Associated With Use of OnabotulinumtoxinA for Treatment of Neurogenic Detrusor Overactivity: A Meta-Analysis - Hejia Yuan; Yuanshan Cui; Jitao Wu; Peng Peng; Xujie Sun; Zhenli Gao (International Neurourology Journal, 2017)
Purpose OnabotulinumtoxinA is used widely for the treatment of neurogenic detrusor overactivity. We conducted a systematic review and meta-analysis to assess its efficacy and safety for neurogenic detrusor overactivity treatment. Methods A systematic literature review was performed to identify all published randomized double-blind, placebo-controlled trials of onabotulinumtoxinA for neurogenic detrusor overactivity treatment. MEDLINE, Embase, and the CENTRAL were employed. Reference lists of retrieved studies were reviewed carefully. Results Six publications involving 871 patients, which compared onabotulinumtoxinA with a placebo were analyzed. Efficacy of onabotulinumtoxinA treatment was shown as a reduction of the mean number of urinary incontinence episodes per day (mean difference, -1.41; 95% confidence interval [CI], -1.70 to -1.12; P<0.00001), maximum cystometric capacity (135.48; 95% CI, 118.22–152.75; P<0.00001), and maximum detrusor pressure (-32.98; 95% CI, -37.33 to -28.62; P<0.00001). Assessment of adverse events revealed that complications due to onabotulinumtoxinA injection were localized primarily to the urinary tract. Conclusions This meta-analysis suggests that onabotulinumtoxinA is an effective treatment for neurogenic detrusor overactivity with localized advent events.